Teaching Principles of Deceased Organ Donation through a Massive Open Online Course - It's Place in the World. (July 2018) - Thomson, David; Muller, Elmi; Jaffer, Tasneem; Nkgudi, Boitumelo; Du Toit, Tinus; Edwardes, Kristi; Walji, Sukaina
Abstract : Introduction: In developing countries there are few transplant programs and insufficient resources to help educate the doctors who are relied upon to identify, refer, and manage donors while communicating with a grieving family. Online education platforms offer a method of teaching medical professionals and the public on a large scale about deceased organ donation best practices. Methods: A 4 week curriculum was constructed with a multiple choice assessment at the end of each week. Content was delivered each week through a series of short videos each between 3 - 10 minutes Reinforcement of learning points was made through regular practice quizzes which gave feedback on all answers. An honours track was added with peer reviewed assignments on "How to break bad news" and "How to improve your local organ donation system". The course was aimed at medical undergraduates completing their final years of training and qualified health professionals looking to learn more about deceased donation. The course was made available on the Coursera platform (https://www.coursera.org/learn/organ-donation ) with a new course running every 4 weeks. Participants earn a course completion certificate by passing all graded assessments and either paying a fee or by applying for financial aid to have the fee waived. Discussion forums were moderated by transplant coordinators and the lead academic. Figure. No caption available. Figure. No caption available. Data were analysed over a 4 month period from July to November 2017 reviewing the demographics, location, gender, age, education and employment status of the course participants as well as the sign up and completion rate and course rating. Results and Discussion: A total of 53 videos, 13 practice quizzes and 4 graded quizzes were created together with 2 peer reviewed assignments. A total of 1537 people viewed the welcome page with 563 signing up for the course. The largest number of participants came from the United States with 21%, followed by South Africa 14%, India 9.5% and Egypt 5.2%. There was an equal distribution between men and women with 74.4% being younger than 34 years of age.Over half (53%) of participants were not formally studying and 21% of participants were unemployed at the time of completing the cours Figure. No caption available. Figure. No caption available. Conclusion: Organ donor education projects using massive open online learning platforms offer an effective means to reach a potentially large audience. This course focused on the science behind organ donation, the ethics and the practicalities of the process with an acceptable completion rate. Marketing support is required. Fiona McCurdie. Maryn Reyneke. Luke Steenkamp. Louise Human. Ivan Joubert. Nawaal Deane. Rondine Carstens. Janet Small .